2020
DOI: 10.5897/ajar2020.15143
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fish consumption in the state of Qatar: Post blockade

Abstract: This study used a count data model to analyse the factors that affect fish consumption in Qatar after the blockade; aiming for effective evaluation, formulation and implementation, of policies for the fishery sector. To achieve this, the community of Qatar is divided into three groups based on their fish consumption rate: high, moderate, and low consumer. The determinants of fish consumption were confirmed using the Poisson model, namely demographic and attitude variables. The findings showed that consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…The only fish species that was reported to be bought frozen was SM. The findings of this study agreed with a previous study where it was reported that the Qatari residents preferred fresh fish over frozen ones (Sana et al, 2020).…”
Section: Fish Consumptionsupporting
confidence: 93%
See 1 more Smart Citation
“…The only fish species that was reported to be bought frozen was SM. The findings of this study agreed with a previous study where it was reported that the Qatari residents preferred fresh fish over frozen ones (Sana et al, 2020).…”
Section: Fish Consumptionsupporting
confidence: 93%
“…The questionnaire was designed to collect information about the frequency and the amounts of fish species consumed during a week time frame, based on a reference period of the previous year. The fish species that were included in the questionnaire were those reported to be the most commonly consumed in Qatar (Sana et al, 2020). These were HM, SF, CH, SH, TU, SM, SB, ANCH, and SAR.…”
Section: Fish Consumption Datamentioning
confidence: 99%